The Problematic of Medicinal Plant: Negative effect of Catha Edulis (Khat) Abuse and Its Potential Benefits - Muflihah Rizkawati; Ulfatun Nisa; Widhi Astana; Leonny Dwi Rizkita (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2023)
Catha edulis (khat), belongs to a group of psychotropic plants, which has an amphetamine-like structure and contains many catin and cation. The plant contains hallucinogenic compounds and known for its calming effect. The excessive catin contained inside the fresh leave of khat could potentially induce a plenty of side effects especially when the leaves are directly consumed and uncooked. The side effects vary according to how long the plant has been consumed, started from local organ disruption to cardiovascular complication such as increased blood pressure to myocardial infarction. In the contrary, positive effects of the composition of khat have also been reported such as anti-inflammatory effect, antidiabetic, anticancer, immunomodulatory and increased improvement in respiratory diseases. Although myriad studies have been conducted to examine the best benefit obtained from the such plant, the legal issue on its utilization is still questionable. Therefore, khat consumption must be maintained with a proper and strong regulation to lessen the negative impacts. However, studies on the potency of khat are still ongoing. The literature review was written based on various books, journals, and search databases in Pubmed, Medline, Cochrane and Google Scholar to show the positive and negative effects of the habit in consuming khat.